2000
DOI: 10.1097/00007632-200010150-00019
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Durotomy in Spine Surgery

Abstract: Incidental durotomy, if recognized and treated appropriately, does not lead to long-term sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
267
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 360 publications
(298 citation statements)
references
References 8 publications
16
267
0
7
Order By: Relevance
“…The risk increase varies between double and fivefold [5,9] and in the paper of Cammisa et al [3], 38% of those with dural lesions had been subjected to 1-6 procedures on the lumbar spine previously. It seems that the risk is higher for less experienced surgeons [15].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The risk increase varies between double and fivefold [5,9] and in the paper of Cammisa et al [3], 38% of those with dural lesions had been subjected to 1-6 procedures on the lumbar spine previously. It seems that the risk is higher for less experienced surgeons [15].…”
Section: Discussionmentioning
confidence: 98%
“…In a large series of spinal procedures [4], it was demonstrated that the morbidity was lower for younger patients and for disc herniation surgery. The risk factors for dural tear and the long-term outcome after such an event have been reported by several authors [1,3,13] but to our knowledge mainly in retrospective studies. In the large prospective SPORT study, an incidence of 4% is related [14].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Instead, the focus of the paper is generally the (positive) surgical outcome of the described procedure, with complications being mentioned in a subordinate paragraph, in the knowledge that ''no complications'' would raise suspicion of biased reporting. The complications listed are usually directly associated with a specific treatment or technique, such as incidental dural tears in decompressive surgery [5,13]. In general, complications are assessed and documented by medical professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Review of the hospital charts after a defined procedure is the methodology most commonly used [5,12,18] and, hence, incidents that can be measured or visualised are usually preferred. The accuracy of placement of pedicle screws [8], dural tears [4,5], and neurological deficit [12] are just a few examples in this category. However, these complications are not necessarily the only ones that concern the patients or influence their satisfaction with treatment/global outcome.…”
Section: Discussionmentioning
confidence: 99%